Dampak Stres kerja, beban Kerja, dan Motivasi Kerja Terhadap Kinerja Karyawan di Bank Pembangunan Daerah Jambi Cabang Tebo - Gustina Marhamah, Sulis; Gusteti, Yesi; Purwanto, Kelik (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2025)
This study looks at the connections between worker motivation, work stress, and work ethics and the Tebo Branch of the Jambi Regional Development Bank. There are forty-five participants in this research sample. After surveys are used to gather the initial data, a regression analysis of the data is carried out. The job stress (X1) does not significantly affect work-related performance, according to the t-test results; the significance is approximately 0.494% (greater than 0.05) and the T-value is roughly -0.690 (less than 0.210). Similarly, a T-hit statistic of -0.275% (lower than 2.020) and a significance of 0.784% (greater than 0.05) suggest that workload (X2) had no discernible impact on caregiver performance. However, research has revealed that work motivation (X3)